Topical cetirizine for treating androgenetic alopecia: A systematic review. (4th September 2022) - Chen, Xiaomei; Xiang, Hongmei; Yang, Ming
Abstract: Background: Cetirizine, a widely used agent for allergic disorders, has recently been topically used for treating androgenetic alopecia (AGA). We aimed to summarize the current evidence regarding the effectiveness and safety of topical cetirizine for treating AGA. Methods: We searched Ovid MEDLINE, Embase, and Cochrane Central Register of Controlled Trials. We included both randomized controlled trials (RCTs) and non‐randomized clinical trials. Findings: We initially identified 102 records, of which, we included two RCTs and one non‐randomized clinical trial, which were of moderate‐to‐high risk of bias. All included trials used 1% topical cetirizine as the intervention with various regimens. Topical cetirizine was likely to be more effective than a placebo for treating AGA. In comparison with topical minoxidil, topical cetirizine appears to be less effective for improving total and vellus hair density, but it might have a longer‐lasting effect. Further, cetirizine might be as effective as minoxidil in improving hair diameter. Conclusion: One percent topical cetirizine may serve as a choice for treating AGA, especially for patients with a negative response to topical minoxidil. In order to fully understand the role of topical cetirizine for AGA, additional well‐designed RCTs are needed.